2014
DOI: 10.1186/1742-4755-11-87
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of fertility in Rwanda in the context of a fertility transition: a secondary analysis of the 2010 Demographic and Health Survey

Abstract: BackgroundMajor improvements to Rwanda’s health system, infrastructure, and social programs over the last decade have led to a rapid fertility transition unique from other African countries. The total fertility rate fell from 6.1 in 2005 to 4.6 in 2010, with a 3-fold increase in contraceptive usage. Despite this rapid national decline, many women still have large numbers of children. This study investigates predictors of fertility during this fertility transition to inform policies that improve individuals’ re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 18 publications
3
28
0
1
Order By: Relevance
“…Their study found an inverse relationship between wealth status and fertility, with significantly lower fertility among the richest women compared to high fertility among the poorest. Similar findings have been reported in [11,32] and [27]. Many other previous studies have focused on the sociocultural and economic determinants of fertility in various regions [11,13,14,18,23,24,27,29,32,34,35].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Their study found an inverse relationship between wealth status and fertility, with significantly lower fertility among the richest women compared to high fertility among the poorest. Similar findings have been reported in [11,32] and [27]. Many other previous studies have focused on the sociocultural and economic determinants of fertility in various regions [11,13,14,18,23,24,27,29,32,34,35].…”
Section: Introductionsupporting
confidence: 89%
“…This study further explained education exposes women to information, empowers women, makes them more likely to be employed outside their home environment, and makes them more aware of their own health and the health of their children-all of which are negatively associated with the number of children a woman will have during her reproductive life. Similarly, educated women are more likely to postpone marriage, have smaller family size, and use contraception than are uneducated women [27]. The value of the odds ratio exp@β E B = 2.0524, for Age at first birth of the mothers that the odds of having TCEB greater than or equal to 5 children for women age 19 and below is 105.24% more than those women aged 25 years and above (OR=2.0524, CI=1.5872-2.6538) and 46.67% for women aged 20-24 years.…”
Section: Resultsmentioning
confidence: 99%
“…No teams submitted a manuscript within 4 months; the first manuscript was submitted within 6 months, two additional manuscripts were submitted within 12 months, a fourth manuscript was submitted at 18 months, and a fifth manuscript was submitted at 26 months to international peer-reviewed journals. At the time of this writing, three manuscripts were published [ 22 24 ], two were under revision to resubmit, and one remained under development.…”
Section: Resultsmentioning
confidence: 99%
“…The latest Rwanda Demographic and Health Survey (RDHS 2014-15) found that teenage pregnancy rate had increased from 4.1% in 2005 to 7.3% in 2015, with the rate in some regions reaching as high as 15.8% (National Institute of Statistics of Rwanda (NISR), Ministry of Health (MOH) [Rwanda], 2015). While many studies have used DHS data to study risk factors related to antenatal care, postnatal care, fertility, and nutrition (Manzi et al, 2014;Mukabutera et al, 2016;Ndahindwa et al, 2014), none have studies those related to teenage pregnancies in Rwanda. Accordingly, this study utilized a secondary data analysis method to identify the risk factors contributing to teenage pregnancies in Rwanda.…”
Section: Introductionmentioning
confidence: 99%